Evaluasi Kualitas Layanan Aplikasi Ujian Digital Menggunakan Metode Webquall 4.0 pada SMA Negeri 1 Semendawai Barat - Deska Novita Sari; Susan Dian Purnamasari; Ilman Zuhri Yadi; Nia Oktaviani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Computer-Based Testing (CBT) application plays a significant role in supporting the learning evaluation process in the modern era. As a technology- based tool, this application enables examinations to be conducted more efficiently, quickly, and in a more structured manner compared to conventional paper-based methods. SMA Negeri 1 Semendawai Barat is a state senior high school located in Kangkung Village, Semendawai Barat Sub-district, Ogan Komering Ulu Timur Regency, South Sumatra Province. The school has implemented information and communication technology (ICT) in its teaching and learning activities, including the administration of examinations through the use of the Bravo Computer-Based Testing (CBT) application to improve the quality of academic evaluations. The use of the Bravo CBT application reflects the school's commitment to keeping pace with developments in educational technology. One method that can be used to evaluate the effectiveness of such applications is WebQual, which is an enhancement of the Servqual method a tool that has long been used in evaluating service quality. WebQual has been adapted specifically to measure the quality of applications or websites through three main dimensions: usability, information quality, and service interaction. Research findings indicate that the variables Usability and Information Quality do not have a significant effect on Service Quality, whereas the Service Interaction Quality variable does have a significant impact on Service Quality.